Predictive modelling of internal pitting corrosion of aged non-piggable pipelines - Ossai, C.; Boswell, B.; Davies, Ian (Electrochemical Society Inc., 2015)
© 2015 The Electrochemical Society. A multivariate regression analysis and time-dependent maximum pit depth growth model was developed using maximum pit depths and pipeline operational parameters, which includes temperature, CO2 partial pressure, flow rate, pH, sulfate ion, chloride ion and water cut. This statistical analysis, which used ten years Ultrasonic Thickness Measurement (UTM) data from non-piggable onshore pipelines, accounted for different categories of maximum pitting rates - low, moderate, high and severe. The model was validated using field data from twelve operating pipelines and the results agreed well with the field data.